Novel Host Range and Cytopathic Variant of Ecotropic Friend Murine Leukemia Virus - Jung, Yong Tae (American Society for Microbiology, 2004)
A variant ecotropic Friend murine leukemia virus, F-S MLV, is capable of inducing the formation of large multinucleated syncytia in Mus dunni cells. This cytopathicity resembles that of Spl574 MLV, a novel variant recently isolated from the spleen of a Mus spicilegus mouse neonatally inoculated with Moloney MLV. F-S MLV is an N-tropic Friend MLV that also has the unusual ability to infect hamster cells, which are normally resistant to mouse ecotropic MLVs. Syncytium induction by both F-S MLV and Spl574 is accompanied by the accumulation of large amounts of unintegrated viral DNA, a hallmark of pathogenic retroviruses, but not previously reported for mouse ecotropic gammaretroviruses. Sequencing and site-specific mutagenesis determined that the syncytium-inducing phenotype of F-S MLV can be attributed to a single amino acid substitution (S84A) in the VRA region of the viral env gene. This site corresponds to that of the single substitution previously shown to be responsible for the cytopathicity of Spl574, S82F. The S84A substitution in F-S MLV also contributes to the ability of this virus to infect hamster cells, but Spl574 MLV is unable to infect hamster cells. Because this serine residue is one of the critical amino acids that form the CAT-1 receptor binding site, and because M. dunni and hamster cells have variant CAT-1 receptors, these results suggest that syncytium formation as well as altered host range may be a consequence of altered interaction between virus and receptor.